Analysis of Slope Stability by the Improved Double-strength Reduction Method Based on Seepage - ZHOU Jintao; XIAO Bowen; JIANG Pengfei; WANG Xuerong; HUANG Yaoxing (Renmin Zhujiang)
Seepage is one of the important factors affecting the slope stability.In order to accurately determine the impact of seepage on the slope,taking the Jiangjiatang slope project in Xingshan,Hubei as an example,this paper introduces the coupling mechanism of seepage and stress fields in rock-soil mass,and compares and analyzes the slope under natural conditions and rainstorm conditions by the improved double-strength reduction method.The results show that the safety factor calculated by the improved dual-strength reduction method under natural conditions is 1.328,while that under rainstorm conditions is 0.97.It can be concluded that seepage has a significant impact on the stability of slope,and the safety factor is reduced by 27% under the coupling of seepage and stress.Therefore,the improved double-strength reduction in the case of seepage can make the calculation results more realistic and provide reference for engineering practice.